The rhetorical aspects of the syntactic element of interjection in the poems of Akhavan_sales - Nasser Alizadeh Khayyat; Azam Roohi Kyasar (مطالعات زبانی و بلاغی)
In addition to its syntactic role in grammar, interjection is an important topic in semantic science. The science of meanings determines the extent to which it is influenced by the audience by measuring the word; hence, it examines the implications of the use of Interjection and its place in the rhetoric of the text. Because semantic science can be adapted to various disciplines of linguistics, in particular, formalism and functionalism, in many respects, the tools of these sciences have also been used in the analysis of this paper. In the present paper, the analytical – descriptive, the issue of exclamations (addressing sentences) together with component roles and different aspects thereof such as addressee delay, omitting interjections, repetition in interjection, combining interrogative and addressing sentences were studied in the works of Mehdi Akhavan Sales (Prominent contemporary poet). Also, the impacts of such components on the rhetorical aspects of the verses in four poetry collections of his (namely: Zemestan (winter), the end of Shahnameh, from this Avesta, Swahili and Khoziat) were taken into account. The results show that Akhavan with full knowledge of the aesthetic aspects of Persian literature andlanguage proficiency of all its features-and considering the subject of an element called - used to deliver the desired concept In changing the position of interjection in his poems, he cares about two axes: the subject and the content of the structure that was originally laid out, as well as the emotional and emotional load on it. By examining the structureshighlighted in the poetry of the Akhavan as well as examining the emotions on them, one can receive the intensity of his interest or hatred towards the subject.